Transfeminist gender perspective in the university training of health sciences professionals in Argentina - Negretti Borga, Dana María (SCT Proceedings in Interdisciplinary Insights and Innovations, 2024)
Feminist Movements warn that there are inequalities based on socio-cultural structures that assign different roles and opportunities to people based on their gender, perpetuating stereotypes limits the full development of women and gender-diverse individuals.(1) Despite the enactment of “Gender Identity” Law 26,743 in Argentina (2012), gender biases, the cisheteronormative approach, and the binary logic in Biomedical and Health Sciences make non-hegemonic identities invisible and stigmatize them, creating risks for their access to integrated health care.(2, 3) Trans, transvestite, and non-binary (TTNB) people continue to face barriers to access and accessibility within the health system, including the lack of training by health professionals to meet their specific needs.(4) From the Endocrinology course at the Faculty of Chemical Sciences of the National University of Córdoba, we promote the training of future health professionals with a trans-inclusive gender perspective,(5) sharing concrete experiences where recognizing TTNB users as subjects of rights, respecting their pronouns and attending specific training promotes greater adherence to treatments, optimizes the use of resources, increases the accuracy of clinical monitoring and improves the biomedical approach to health. In conclusion, we support the advancement of the mainstreaming of the non-binary gender perspective in the teaching and learning processes in the curricula of future health professionals, promoting comprehensive and equitable biomedical care for the entire population